2009
DOI: 10.1007/s00701-009-0540-x
|View full text |Cite
|
Sign up to set email alerts
|

A new approach to the treatment of cerebral vasospasm: the angiographic effects of tadalafil on experimental vasospasm

Abstract: Our study results showed that tadalafil has a vasodilatory effect on both acute and chronic periods of cerebral vasospasm. We also concluded that cerebral angiography can be used safely for investigation of cerebral vasospasm in animal studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…First, we found that post-SAH initiation of sildenafil attenuates vasospasm in an endovascular perforation SAH model, which confirms previous cisterna magna injection SAH studies. 5–6, 8 Second, we document that sildenafil improves neurological outcome after SAH – a critical finding given that numerous studies have shown a dissociation between the vascular and functional benefits of certain SAH therapeutics. 2122 Third, we found that sildenafil reduces SAH-induced neuronal cell death, which may reflect a reduction in vasospasm-induced ischemia or a direct neuroprotective effect (or both).…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…First, we found that post-SAH initiation of sildenafil attenuates vasospasm in an endovascular perforation SAH model, which confirms previous cisterna magna injection SAH studies. 5–6, 8 Second, we document that sildenafil improves neurological outcome after SAH – a critical finding given that numerous studies have shown a dissociation between the vascular and functional benefits of certain SAH therapeutics. 2122 Third, we found that sildenafil reduces SAH-induced neuronal cell death, which may reflect a reduction in vasospasm-induced ischemia or a direct neuroprotective effect (or both).…”
Section: Discussionmentioning
confidence: 67%
“…Studies to date show the following: 1) acute administration of sildenafil partially relaxes basilar artery vasospasm in dogs 7 ; 2) pre-SAH initiation of sildenafil partially inhibits vasospasm in rabbits 4 ; and 3) post-SAH initiation of sildenafil and other PDE5 inhibitors attenuates vasospasm in rat cisterna magna models of SAH. 568 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Vasospasm was detected immediately after SAH (30 mins) but not thereafter, indicating that vasospasm is transient in this mild SAH model. Previous studies using ex vivo arteries 4143 and in vivo angiography 44,45 in relatively more severe SAH models have detected vasospasm. Specifically, an MRI study of a SAH model by puncturing the vessel found narrowing of vessels but vasoconstriction only reached significance in the right proximal ICA in the acute phase and returned to normal on day 9.…”
Section: Discussionmentioning
confidence: 97%
“…Intrathecal administration of a cell-membrane permeant form of cGMP prevented hemorrhage-associated hemodynamic changes in one rodent model [75]. Additionally, phosphodiesterase-5 inhibitors prevented vasospasm in rodent models [76, 77]. However, these approaches have yet to be explored in human studies.…”
Section: Treatment Of Vasospasmmentioning
confidence: 99%